Analisis Pendekatan Rules of Reason dalam Kasus Praktik Predatory Pricing (Studi Kasus Putusan Nomor 03/KPPU-L/2020) - Vincentius Eric Sutanto (Universitas Batanghari Jambi, 2023)
The practice of predatory pricing is the act of a business actor to get rid of or hinder a competitor’s business in the relevant market share by selling at a loss or setting a very low price. Conch South Kalimantan Cement Limited Company was reported on suspicion of predatory pricing practice. The allegation report is based on Article 20 of Indonesian Law Number 5 of 1999. In the formulation of the article, the rules of reason approach are used. In the rules of reason approach, even if a business actor is proven to have practiced predatory pricing, it is still possible to be declared innocent. This is because in the rules of reason approach, Komisi Pengawas Persaingan Usaha first looks for the predatory pricing that cause anti-competition in market shares or not. As long as it does not cause anti-competition and supports business competition, Conch South Kalimantan Cement Limited Company cannot be sanctioned and found not guilty. Komisi Pengawas Persaingan Usaha after using rules of reason approach finally stated Conch South Kalimantan Cement predatory pricing practice cause anti-competition and give it sanction.